Successful joint venture at United Engineers Malaysia (Berhad) / Nureliana Abdul Rahman - Abdul Rahman, Nureliana (Faculty of Business and Management, 2010)
This case study exploring the International Joint Venture and the theories. Another objective of the joint venture of the Company is to establish the business against all identified risk. Next, the Company should continuously improve to select the best partner selection and more beware in the big project. The main issue of this study is to explore the problem the design and more punctual in project from happening in the future. This issue deeply explained in the report in order to be more clarifying for understanding of international joint venture.